CONSUMER PREFERENCE ON DEMAND FOR LOCAL, IMPORTED FROZEN AND FRESHLY SLAUGHTERED CHICKEN MEAT IN IFE/IJESA SENATORIAL DISTRICT OF OSUN STATE - ADEDIRE, A.O.; AKINTUNDE, O. K.; AKINTUNDE, O. K.; BAMIWUYE, O. A.; ALUKO, O. P.; ALUKO, O. P.; ORUMA , A. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
Chicken meat is considered an easily available source of high-quality protein that is necessary for proper body functioning and growth. This study investigated consumer preference on demand for local frozen (LF), imported frozen (IF), and freshly slaughtered (FS) chicken meat in Ife/Ijesa Senatorial District of Osun State, Nigeria. Data used for the study were obtained from 200 respondents randomly selected from four Local Governments which include Ife East, Central, Ilesa East, and Obokun. Data obtained were analyzed using descriptive statistics with the aid of SPSS version 20 and STATA. The findings of the study revealed that 40% of the consumers claimed that they preferred LF chicken which is largely influenced by health, cost, and convenience. A paired t-test revealed that there is a significant difference in the consumption of LF and IF chicken (t = 2.45) while there is no significant difference in the consumption of LF and FS chicken (t = 1.03). Sensory evaluation tested on a nine-point hedonic scale revealed that consumers preferred most LF chicken with a Weighted Mean Score (WMS = 7.13) above others. The study revealed that purchase decisions were mostly based on price (WMS = 4.6) followed by health attributes (WMS = 4.06), and convenience attributes (WMS = 3.97). The authors concluded that there is an opportunity to explore LF chicken production and market due to its acceptability over other chicken meat types. Therefore, people should invest in the poultry industry, across the supply chain from processing to marketing of local chicken.